2018
DOI: 10.1007/s00705-018-3992-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and phylogenetic analysis of newly discovered bat astroviruses in Korea

Abstract: Bats have been identified as a natural reservoir for several potentially zoonotic viruses. Recently, astroviruses have been reported in bats in many countries, but not Korea. We collected 363 bat samples from thirteen species at twenty-nine sites in Korea across 2016 and tested them for astrovirus. The detection of the RNA-dependent RNA polymerase (RdRp) gene in bat astroviruses was confirmed in thirty-four bats across four bat species in Korea: twenty-five from Miniopterus fuliginosusi, one from Myotis macrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The coexistence of at least two distinct CoV genomes in one bat was reported in Lau et al 8 and Chu et al 28 . In addition, a genetic hyperpolymorphism between astrovirus haplotypes detected from one bat was reported in Lee et al 7 . In this study, we first identified the multiple infection of viruses of different genera in an individual bat.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The coexistence of at least two distinct CoV genomes in one bat was reported in Lau et al 8 and Chu et al 28 . In addition, a genetic hyperpolymorphism between astrovirus haplotypes detected from one bat was reported in Lee et al 7 . In this study, we first identified the multiple infection of viruses of different genera in an individual bat.…”
Section: Discussionmentioning
confidence: 72%
“…In 2015, the first bat-derived viruses in the Republic of Korea (ROK) were discovered from bat fecal samples: coronaviruses, group H rotavirus, bunyavirus, and Banna virus 14 . Following this, alphacoronavirus, betacoronavirus, astrovirus, and paramyxovirus have also recently been reported 7,19,20 . Considering that the viruses detected in bats globally belong to more than 29 families 17 , it is estimated that only a small number of bat viruses have Detection of bat picornaviruses within various genera from 16BF77.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…They may carry both host-restricted astroviruses as well as more diverse strains closely related to other members of the mamastrovirus genus, such as fox, murine, ovine, mink and human AstVs and even avian astroviruses of the avastrovirus genus. Phylogenetic analyses of the partial genome revealed a significant strain diversity of bat astroviruses forming numerous recognized and proposed species [ 6 , 14 , 15 , 16 , 17 ], supposedly generated both by intraspecies and interspecies recombination as well as interspecies transmission [ 18 ]. The high prevalence of diverse astrovirus strains from multiple hosts suggests that bats play a key role in astrovirus diversity and interspecies transmission [ 18 ].…”
Section: Introductionmentioning
confidence: 99%